Snoring Is Associated With Increased Risk of Stroke: A Cumulative Meta-Analysis - Bai, Jing; He, Bing; Wang, Nan; Chen, Yifei; Liu, Junxiang; Wang, Haoran; Liu, Dongliang (Frontiers in Neurology, 2021)
Background: Several studies have suggested that snoring is associated with an increased risk of stroke; however, the results are inconsistent. We aim to conduct a systematic review and meta-analysis of observational studies assessing the association between snoring and risk of stroke in adults. Methods: We searched PubMed for relevant studies. Random-effects model was adopted to summary relative risks (RRs), and forest plots from a cumulative meta-analysis method was used for a better presentation of how the pooled RRs changed as updated evidence accumulated. Results: The literature search yielded 16 articles that met our inclusion criteria, and a total of 3,598 stroke patients and 145,901 participants were finally included in our analysis. A consistent trend toward association was found after the initial discovery, and the summary analysis indicated that snoring is associated with a 46% (RR, 1.46; 95%CI, 1.29-1.63; p<0.001) increased risk of stroke. Conclusions: Snoring is associated with a significantly increased risk for stroke, up to 46%. The importance of the current study lies in that we provide an imputes to take a more active approach against the increased risk of stroke in snorers.